2020
DOI: 10.1002/cncr.33139
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence and survival probability after second recurrence of retroperitoneal sarcoma: A study from TARPSWG

Abstract: BACKGROUND: In this series from the Transatlantic Australasian Retroperitoneal Sarcoma Working Group (TARPSWG), the authors examined longitudinal outcomes of patients with a second recurrence of retroperitoneal sarcoma (RPS) after complete resection of a first local recurrence (LR). METHODS: Data from patients undergoing resection of a first LR from January 2002 to December 2011were collected from 22 sarcoma centers. The primary outcome was overall survival (OS) after second recurrence. RESULTS: Second recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…62.5% of distant relapses was in the lung followed by nodes (18.8%) and liver (12.5%). These patterns of relapse have been reported in studies ( 24 , 25 ). Similarly, in the developmental Italian cohort, recurrence patterns were specific to histological subtype with liposarcoma having the highest 6-year crude-cumulative incidence (CCI) of second local recurrence at 60.2% to 70.9% while LMS had a higher 6-year CCI of distant metastasis at 36.3% ( 16 ).…”
Section: Discussionsupporting
confidence: 84%
“…62.5% of distant relapses was in the lung followed by nodes (18.8%) and liver (12.5%). These patterns of relapse have been reported in studies ( 24 , 25 ). Similarly, in the developmental Italian cohort, recurrence patterns were specific to histological subtype with liposarcoma having the highest 6-year crude-cumulative incidence (CCI) of second local recurrence at 60.2% to 70.9% while LMS had a higher 6-year CCI of distant metastasis at 36.3% ( 16 ).…”
Section: Discussionsupporting
confidence: 84%
“…This is very unlikely and is in direct contradiction to the main studies, which reported twice as many local relapses after mCR in the surgery group compared with the preoperative‐RT group (47 vs 23 relapses). Compliance to RT might have a long‐term impact on local control, and this could only be assessed by following these patients longer. Indeed, long‐term recurrences are common in this setting 11‐13 Leaving out a part of the tumor (eg, mostly well differentiated part) might not affect local control, especially for cases in which the nondelineated part could be resected during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, long-term recurrences are common in this setting. [11][12][13] • Leaving out a part of the tumor (eg, mostly well differentiated part) might not affect local control, especially for cases in which the nondelineated part could be resected during surgery. This would have a major impact on the analysis because incorrect target delineation was the most common reason for unacceptable overall RT compliance, of which 64% was caused by gross tumor volume miss.…”
Section: Discussionmentioning
confidence: 99%
“…Because of metastasis, multifocal disease, and multiple organ resection are usually contraindications to surgery, the potential bene cial effects of surgery are not always obvious, which lead decision-making very complicated. Because of metastasis, multifocal tumor, and multiple organ resection are usually contraindications to surgery [14]. And it is extremely di cult for clinical decision-making whether or not patients with recurrence should undergo surgery.…”
Section: Discussionmentioning
confidence: 99%